Dinámica poblacional de los principales insectos plagas asociados al maíz con relación a las fases fenológicas del cultivo - Castro Mena, Yosselin Ariana (2021)
The identification of insect pests in economically important crops such as corn helps in decision-making for the application of timely control methods, so that economic and productive losses are reduced. That is why the present research aimed to determine the incidence of the main insect pests associated with corn in relation to the phenological phases of the crop. Evaluations were carried out in four localities of the Mocache canton: Pechiche, Barro Colorado, Jesús del Gran Poder and Las Palmas. The insects were monitored in an area of 1000 m2, by the entomological network methods, direct capture in plants and adhesive traps, making records in 3 stages in phenological phases (emergence, vegetative and reproductive phase). The insects captured by orders were classified using descriptive statistical methods, in addition a count of the insects collected with each capture method was made and the incidence of both pests and beneficial insects was determined. The results obtained show that, throughout the vegetative cycle of the corn crop, insect pests of the orders were identified: Thysanoptera, Hemiptera, Diptera, Lepidoptera, Orthoptera, Coleoptera and Hymenoptera, highlighting the hemipterans that exceeded 600 specimens per location. In the Mocache canton, the insects associated with the cultivation of corn were: S. frugiperda, D. saccharalis, D. maidis, A. ipsilon and M. persicae, which was reflected in the four locations under study, of which D. maidis showed a higher occurrence in each of the localities, with up to 14, 11, 17, 9 and 7 specimens per stage, respectively. In the four evaluated localities it was observed that S. frugiperda and D. saccharalis did not show incidence in the crop emergence stage, while both S. frugiperda, D. saccharalis, D. maidis, A. ipsilon and M. persicae. the incidence was higher in the vegetative stage, with values between 29.41 and 66.67%. The presence of the beneficial insects H. convergens, C. sanguinea, Euplectrus sp., C. tricolor, Polistes sp, was identified with up to 4 specimens per locality, acting as predators of eggs and larvae of S. frugiperda and D. saccharalis, and C. insularis as parasitoid S. frugiperda. The beneficial species H. convergens showed greater abundance of specimens in all localities, with between 3 and 4 specimens. Keywords: Pest management, Pest insects, Beneficial insects.